2014
DOI: 10.1002/tox.21989
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract ofHedyotis diffusawilld upregulates G0/G1 phase arrest and induces apoptosis in human leukemia cells by modulating caspase cascade signaling and altering associated genes expression was assayed by cDNA microarray

Abstract: The authors' previous study has shown that water extract of Hedyotis diffusa Willd (HDW) promoted immune response and exhibited anti-leukemic activity in BALB/c leukemic mice in vivo. In this study, the anti-proliferation effects of ethanol extract of H. diffusa Willd (EEHDW) on lung cancer cell lines (A549, H1355, and LLC), leukemia cell lines (HL-60, WEHI-3), and a mouse melanoma cell line (B16F10) in vitro were investigated. The results demonstrated that EEHDW suppressed the cell proliferation of A549, H135… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…But this effect was not found in LLC cells [66]. Further, Shi et al [38] confirmed that two compounds of 2-hydroxy-3-methyl anthraquinone (IC 50 66 µM) and 2-hydroxy-1-methoxy anthraquinone (IC 50 79 µM) from H. diffusa could induce apoptosis on SPC-1-A cells with a close relationship to the mitochondrial apoptotic pathway.…”
Section: Anti-lung Cancer Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…But this effect was not found in LLC cells [66]. Further, Shi et al [38] confirmed that two compounds of 2-hydroxy-3-methyl anthraquinone (IC 50 66 µM) and 2-hydroxy-1-methoxy anthraquinone (IC 50 79 µM) from H. diffusa could induce apoptosis on SPC-1-A cells with a close relationship to the mitochondrial apoptotic pathway.…”
Section: Anti-lung Cancer Activitymentioning
confidence: 98%
“…H. diffusa aqueous extract treatment with 0.01-4150 µg/mL restrained the growth of the CEM cells by enhancing the expression of P53 in vitro [63] and influenced murine leukemia WEHI-3 cells, as well as promoting T-and B-cell proliferation in leukemic mice administrated with 16 and 32 mg/kg in vivo [64]. The ethanolic extract of H. diffusa could trigger an arrest of HL-60 cells at the G 0 /G 1 phase and sub-G 1 population, provoke DNA condensation and DNA damage, but elevate the activities of caspase-3, caspase-8 and caspase-9, thus, inhibiting the cell proliferation of HL-60 cells with the half maximal inhibitory concentration (IC 50 ) value of 4.62 mg/mL [65,66]. Wang et al [67] found that 2-hydroxy-3-methyl anthraquinone treatment (0-80 µM) could enhance apoptosis of U937 cells in a dose-dependent manner through the activation of p-p38MAPK and downregulation of p-ERK1/2.…”
Section: Anti-leukemia Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hedyotis diffusa willd and some of its active constituents have gained increasing attention as an antitumor herb in liver, lung, prostate, colon, brain, pancreas and other cancers (40). The ethanol extract of Hedyotis diffusa willd could upregulate G0/G1 phase arrest and induce apoptosis in human leukemia cells by modulating caspase cascade signaling and altering the gene levels related to cell growth, signal transduction, apoptosis, cell adhesion, cell cycle, DNA damage and repair, transcription and translation by cDNA microarrays (41). The ethanol extract of Hedyotis diffusa willd also could inhibit colorectal cancer growth in mice though the STAT3 pathway without apparent adverse effects (42).…”
Section: Hedyotis Diffusa Willdmentioning
confidence: 99%
“…However, there is limited literature available regarding their applications against human MM. Only two previous studies reported that water extract of S. nigrum inhibited the metastasis of mouse melanoma B16-F1 cells and the ethanol extract of H. diffusa suppressed the growth of mouse melanoma B16-F10 cells 29,36. To evaluate the applicability of these four herbs in treating MM, we measured the cyto-toxicity of their water extracts toward MM cell line A-375.…”
Section: Resultsmentioning
confidence: 99%